RS Onkologi Surabaya (Boutique Hospital Concept), An Alternative Model for Secondary Care - Djatmiko, Ario (Indonesian Journal of Cancer, 2009)
https://www.scribd.com/doc/45501919/RS-Onkologi-Surabaya-Boutique-Hospital-Concept-An-Alternative-Model-for-Secondary-Care